A study of end milling process parameter's effect on thin wall aluminum-7075 surface roughness under minimum quantity lubrication - Arif, Wahjudi; Ahmad Razlan, Yusoff; Sabil, Sabil; Soepangkat, Bobby O. P.; Suhardjono, Suhardjono (Malaysian Tribology Society (MYTRIBOS), 2024)
The end milling process on thin wall aluminum-7075 under minimum quantity lubrication, as an effort to apply clean technology, has been carried out in this research to obtain the effect of process parameters and lubricant spraying direction on surface roughness. The parameters applied to the process were spindle speed, feeding speed, and depth of cut, while the spraying directions used were in the same and opposite directions of feeding. Statistical analysis was then applied to predict surface roughness values in each combination of parameter levels. All parameters except spindle speed have a significant effect on surface roughness. The prediction equations have MSE values of 1.54×10-3 µm2 and 7.03×10-3 µm2 for the direction of spraying lubricants in the same and opposite directions of feed, respectively.